A Silver‐Free, Reflective Substrate Electrode for Electron Extraction in Top‐Illuminated Organic Photovoltaics. Issue 6 (18th February 2015) - Tyler, Martin S.; Hutter, Oliver S.; Walker, Dr Marc; Hatton, Dr Ross A.
Abstract: The choice of metals suitable as the reflective substrate electrode for top‐illuminated organic photovoltaics (OPVs) is extremely limited. Herein, we report a novel substrate electrode for this class of OPV architecture based on an Al | Cu | AlO x triple‐layer structure, which offers a reflectivity comparable to that of Al over the wavelength range 400–900 nm, a work function suitable for efficient electron extraction in OPVs and high stability towards oxidation. In addition to demonstrating the advantage of this composite electrode over Al in model top‐illuminated OPVs, we also present the results of a photoelectron spectroscopy study, which show that an oxidised 0.8 nm Al layer deposited by thermal evaporation onto an Al | Cu reflective substrate electrode is sufficient to block oxidation of the underlying Cu by air or during deposition of a ZnO1− x electron‐transport layer. This is remarkable given that the self‐limiting oxide thickness on Al metal is greater than 2 nm. Abstract : On reflection: A new substrate electrode for top‐illuminated organic photovoltaics that combines a low work function with a reflectivity comparable to that of aluminum and high stability towards oxidation (see figure) has been fabricated, which uses low‐cost earth‐abundant materials—a rare combination of properties that is rationalized using core‐level photoelectron spectroscopy.